The Analysis of the Teacher-Made Multiple-Choice Tests Quality for Natural Science Subject - Putra, Erik Nanda; Syamsurizal, Syamsurizal; Lufri, Lufri; Zulyusri, Zulyusri (Journal of Education Research and Evaluation, 2021)
This study aims to determine the quality of the questions quantitatively (reliability, discriminating power, difficulty level, and distractor effectiveness). This research is descriptive research. The population in this study were all student answer sheets in the Middle Semester II Science Assessment Exam class VIII SMP Negeri 2 Koto XI Tarusan Academic Year 2020/2021. The sampling technique used total sampling with a sample size of 107 student answer sheets. Data were analyzed using ANATES ver. 4.0.2 program. Based on the research results obtained: 1) reliability of 0.50 with sufficient criteria; 2) the distinguishing power of the bad and good categories which dominates, namely 30% while 25% is moderate and 7.5% is very good; 3) the level of difficulty obtained by the criteria was medium with 62.5%, while the easy questions were 15%, the difficult questions were 12.5% and the very difficult questions were 2.5%; 4) the effectiveness of the distractor, there were 35 items or 87.5% of the effectiveness of the distractor which was functioning properly. Meanwhile, for 5 items, the quality of the distractor does not function or has very poor effectiveness. Thus, it can be concluded that these questions have met the criteria for good questions, but some questions need to be revised.